ANALISA PENGARUH KEPEMILIKAN INSTITUSIONAL, PROPORSI DEWAN KOMISARIS INDEPENDEN, DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019) - Rita Andini; Arditya Dian Andika; Ari Pranaditya (Jurnal Akuntansi dan Pajak, 2022)
Empirical data between the target and the realization of tax revenue in Indonesia from 2014 to 2019 is very volatile, even the phenomenon tends to decrease, namely in 2015, 2017, and 2019. In 2015 there was a significant decline from the previous year of 10.40 %. Thus, attention is needed and an adequate handling system by the tax authorities is needed. Research aims to analyze the variables that influence taxpayers to do tax avoidance. Some of the variables that are thought to be able to influence it are; Institutional Ownership, Proportion of Independent Commissioners, and Profitability with Company Size as Moderating Variable. Population in this study are companies in the food consumption goods industry sector listed on the Indonesia Stock Exchange for the 2015-2019 period. The sample in this study using purposive sampling method obtained a sample of 100 (20 x 5 years), while the number of companies that meet the criteria is 20. Variable consists of five variables; Institutional Ownership, Proportion of Independent Commissioners, and Profitability as independent variables, Firm Size as the moderating variable, while Tax Avoidance as the dependent variable. The method of data analysis was done by testing the hypothesis (t-test), and testing the moderating variable using MRA (Moderated Regression Analysis). Study resulted in conclusions1. Institutional ownership has no positive and significant effect on tax avoidance, with a sig value of 0.247. Proportion of Independent Commissioners has no positive and significant effect on tax avoidance, with a sig value of 0.293. Profitability has a negative and significant effect on tax avoidance, with a sig value of 0.015. Firm size does not strengthen the relationship between institutional ownership and tax avoidance, the results of the interaction test show the value of sig. of 0.343. Company size does not strengthen the relationship between the proportion of Independent Commissioners and tax avoidance, the results of the interaction test show the value of sig. of 0.293. Firm size strengthens the relationship between profitability and tax avoidance, the results of the interaction test show the value of sig. of 0.013